Parents’ and caregivers’ role toward childhood vaccination in Albania: assessment of predictors of vaccine hesitancy - Gjini, E.; Moramarco, S.; Carestia, M. C.; Cenko, F.; Ylli, A.; Mehmeti, I.; Palombi, L.; Buonomo, E. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Vaccination has saved millions of lives through the protection of individuals and populations from communicable diseases. Vaccine hesitancy, defined as the delay in acceptance or refusal of vaccines despite the availability of vaccination services, has become a growing global concern. The objective of this study was to investigate parents’/caregivers’ hesitancy toward childhood vaccination and its predictors in Albania. Study design. A cross-sectional survey was conducted. Methods. The data comes from a survey conducted on a sample of parents/caregivers (89.6% mothers) of children aged 6 months to 8 years at health care vaccination centers in seven Albanian cities from December 2020 to February 2021. Parents/caregivers (one per child) were interviewed by trained healthcare staff using a standardized questionnaire on six main content domains, including immunization behavior, beliefs about vaccine safety and efficacy, attitudes about vaccines, vaccination confidence, estimation of vaccine delay, and the intention to immunize children against SARS-CoV-2, and a self-reported hesitancy. The Albanian Ministry of Health approved the questionnaire, after it was translated, validated and adapted to the local setting. Statistical analyses included independent sample t-tests (p<0.05) and a logistic regression (OR; 95% C.I.). Results. A total of 475 parents/caregivers of children aged from 6 months to 8 years, attending childhood vaccination in public health services, were interviewed. To the question “how hesitant you are about childhood vaccination”, a high number of parents/caregivers (46%) responded that they do not feel hesitant at all, and 32% were not hesitant, a small number of parents/caregivers said they are very hesitant (5%) or somewhat hesitant (12%). A binary logistic model was fitted to the data to test the hypothesis regarding the relationship between parental vaccine hesitancy and possible predictors. A lower parental attitude toward childhood vaccines (OR = 3.7; 95% C.I. 1.102-12.421), a health center with a high vaccine delay (OR = 2.878; C.I. 95% 1.735-4.773), and low confidence in health staff information (OR = 2.042; 95% C.I. 1.156-3.605) were all independent predictors of parental vaccine hesitancy. Regarding intention to vaccinate children against COVID-19, when available, nearly 75% of parents/caregivers showed hesitancy. Conclusions. Our results highlighted the role of positive parents’/caregivers’ attitudes toward childhood vaccines followed by high staff confidence and good health center organization in order to deal with vaccine hesitancy, particularly for traditional and well-known childhood vaccines. Nevertheless, the hesitancy can be a critical barrier for childhood vaccination when we have to introduce a new vaccine, as is demonstrated in the recent vaccination campaign against the ongoing pandemic of SARS-CoV2.